Antimycotic Activity Potentiation of Allium sativum Extract and Silver Nanoparticles against Trichophyton rubrum. Issue 4 (5th March 2019) - Robles‐Martínez, Marissa; González, Juan Fernando Cárdenas; Pérez‐Vázquez, Francisco Javier; Montejano‐Carrizales, Juan Martín; Pérez, Elías; Patiño‐Herrera, Rosalba
Abstract: A natural and biocompatible extract of garlic as a support, decorated with silver nanoparticles, is a proposal to generate an effective antifungal agent against dermatophytes at low concentrations. Silver nanoparticles (AgNPs) with a diameter of 26±7 nm were synthesized and their antimycotic activity was examined against Trichophyton rubrum ( T. rubrum ), inhibiting 94 % of growth at a concentration of 0.08 mg ml −1 . Allium sativum (garlic) extract was also obtained ( As Ext), and its MIC was 0.04 mg ml −1 . To increase the antifungal capacity of those systems, As Ext was decorated with AgNPs, obtaining As Ext‐AgNPs. Using an As Ext concentration of 0.04 mg ml −1 in independent experiments with concentrations from 0.01 to 0.08 mg ml −1 of AgNPs, it was possible to inhibit T. rubrum at all AgNPs concentrations; it proves a synergistic effect between AgNPs and As Ext. Even if 1 % of the minimum inhibitory concentration of As Ext (0.0004 mg ml −1 ) is used, it was possible to inhibit T. rubrum at all concentrations of AgNPs, demonstrating the successful antimycotic activity potentiation when combining As Ext and AgNPs. Abstract :